Implementasi Cobit 4.1 Domain Deliver and Support (DS) Terhadap Tata Kelola Teknologi Informasi (Studi Kasus: Dinas Komunikasi dan Informatika Kabupaten Tulungagung) - Danny Esfarditya; Suprapto Suprapto; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Department of Communication and Information Tulungagung (Diskominfo) is an institution that has the main function of formulating policies, evaluating and reporting in the field of communication and information service. But, in its implementation is still not optimal and there are constraints on the delivery and support of IT services such as the lack of references and of procedures in several processes that causes the process is not running optimally, the existing human resources are still inadequate in terms of skills and numbers. Diskominfo Tulungagung has never evaluated IT governance before. Therefore, an evaluation of information technology governance is needed using the COBIT 4.1 platform of Deliver and Support (DS) domains. The purpose of this study is to obtain the maturity level that obtained from the results of questionnaires and interviews with correspondents based on RACI Chart. The gap value is calculated between the current maturity level and what is expected by diskominfo. Based on previous calculations, recommendations is produced. From the results of the maturity level calculation, the average result of the DS domain is 1.50 and the gap value is 1.00 until 3.00. To achieve the expected maturity level, researchers provide recommendations in the form of suggestions that are doing good planning, formally documenting and making a Standard Operating Procedure (SOP) document for each DS domain process. These are recommendations are expected to be implemented by field of E-Government Organization to achieve goals in better management of IT services.